Treating feeding challenges in autism : turning the tables on mealtime - Tarbox, Jonathan, active 2014 (Critical specialties in treating autism and other behavioral challenges., 2017)
Treating Feeding Challenges in Autism: Turning the Tables on Mealtime distills existing research on feeding disorders treatment into the very best, most effective and most practical strategies for practitioners to implement with their clients who have autism and other developmental and behavioral disorders. The book focuses on the few but highly effective feeding treatment procedures that work in the large percentage of cases. The book describes each procedure in practical, how-to language, with the goal of explaining how to implement them in the real-life settings in which practitioners actually work. The book includes a large variety of sample datasheets, intervention plans and graphs of sample data to serve as practical examples to guide clinicians through the process of selecting, implementing, analyzing and troubleshooting feeding interventions.